Potensi limbah kulit buah Nyirih Xylocarpus granatum sebagai inhibitor tirosinase - Mohamad Gazali; Neviaty P Zamani; Irmanida Batubara (Depik, 2014)
The aim of the present study was to analyse the peel waste of Xylocarpus granatum fruits as potential source of tyrosinase inhibitors. Dried peel samples were ground to yield a powder (simplicia). Subsequently, they were extracted with organic solvents of distinct polarity levels, namely n-hexane (non-polar), chloroform (semi-polar) and methanol (polar) by use of the single-maceration method. Inhibitory effects on tyrosinase activity (monophenolase) and DOPA auto-oxidation (diphenolase) were determined in bioassays. Assays with the methanol extract revealed IC50 values of 784.87 g mL-1 (monophenolase) and of 1176.66 g mL- 1 (diphenolase), respectively. In contrast, n-hexane and chloroform extracts showed no activity. These results indicate that the methanolic fruit peel extract contained tyrosinase-inhibiting compounds, such as flavonoids, tannins and saponins, whereas the nhexane and chloroform extracts yielded alkaloids, steroids and triterpenoids without tyrosinase-inhibiting activity. The phenolic compounds had a strong effect on the tyrosinase enzymes, inhibiting monophenolases by 97% and diphenolases by 96%, with a positive correlation between the total phenolic content and the inhibition rate in both activities.Penelitian ini bertujuan untuk menganalisis kulit buah Xylocarpus granatum sebagai sumber potensial inhibitor tirosinase. Sampel kering digiling untuk menghasilkan (serbuk) simplisia. Berikutnya, simplisia diekstraksi dengan pelarut organik dengan tingkat kepolaran yaitu n-heksana (non polar), kloroform (semi polar) dan metanol (polar) dengan menggunakan metode maserasi tunggal. Pengaruh inhibisi didalam aktivitas tirosinase (monofenolase) dan auto-oksidasi DOPA (difenolase) ditentukan di dalam uji. Uji ekstrak metanol menunjukkan masing-masing nilai IC50: 784,87 g mL-1 (monofenolase) dan nilai IC50: 1176,66 g mL- 1 (difenolase). Sebaliknya, ekstrak n-heksana dan kloroform menunjukkan tidak ada aktivitas. Hasil penelitian ini menunjukkan bahwa ekstrak metanol kulit buah X. granatum mengandung senyawa-senyawa yang menghambat aktivitas tirosinase seperti flavonoid, tanin dan saponin sedangkan ekstrak n-heksana dan kloroform menghasilkan senyawa alkaloid, steroid, dan triterpenoid tanpa penghambatan aktivitas tirosinase. Senyawa fenolik mempunyai pengaruh kuat dalam menginhibisi enzim tirosinase baik aktivitas monofenolase sebesar 97% dan aktivitas difenolase sebesar 96% dengan korelasi positif antara kandungan total fenol dan tingkat inhibisi pada kedua aktivitas